Variability in the international normalised ratio (INR) in patients with antiphospholipid syndrome and positive lupus anticoagulant: Should the INR targets be higher? (2015)
We present the case of a 34-year-old woman with a history of antiphospholipid syndrome with triple positivity for antiphospholipid antibodies, who had multiple thrombotic events, predominantly pulmonary embolic events, despite treatment with enoxaparin. She is currently on warfarin, with which she has been adequately controlled most of the time, presenting with only one haemorrhagic event consisting of haematuria and prolonged international normalised ratio (INR) without bleeding. This kind of patient represents a challenge for clinicians, particularly due to INR therapeutic targets, which should be higher than recommended in other patients due to the lupus anticoagulant positivity.